Determination of Comfortable Outdoor Spaces in Mass-Housing Settlements in Terms of Wind and Noise Control - Kiraz, Fatih; Zorer Gedik , Gülay; Yüğrük Akdağ, Neşe; Şener, Bekir; Çaçan, Raşide (ICONARCH International Congress of Architecture and Planning, 2014)
In recent times, pre-analysis and necessary precautions and measures on wind and noises are ignored and cannot be reflected in design process of indoor and outdoor spaces. In mass housing apartments, the comfort and quality of living conditions decrease due to the wind and noise level especially in balconies, terraces, gardens and swimming pools etc. The quantitatively and empirically testing of building models according to the physical conditions in regard to the wind and noise parameters directly affect the formation of building blocks in design process. In Yıldız Technical University, a research project supported by TUBITAK has been completed in order to determine the most suitable settlement formations and to develop a methodology for a design guide to deal with the controlling of the wind and noise conditions. This paper aims to present spatial formation solutions to provide usage areas in maximum comfort level due to the conditions of different climate zones and different building orientations in terms of wind and noise in Istanbul case.